2017
DOI: 10.1142/s0192415x17500665
|View full text |Cite
|
Sign up to set email alerts
|

Rhodiola crenulata Attenuates High Glucose Induced Endothelial Dysfunction in Human Umbilical Vein Endothelial Cells

Abstract: Rhodiola crenulata root extract (RCE), a traditional Chinese medicine, has been shown to regulate glucose and lipid metabolism via the AMPK pathway in high glucose (HG) conditions. However, the effect of RCE on HG-induced endothelial dysfunction remains unclear. The present study was designed to examine the effects and mechanisms of RCE against hyperglycemic insult in endothelial cells. Human umbilical vein endothelial cells (HUVECs) were pretreated with or without RCE and then exposed to 33[Formula: see text]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…In this study, we observed that RCE rescued endothelial NO production and signaling via AMPK-AKT-eNOS axis under hypoxia. This is consistent with our previous studies demonstrating that RCE counteracts the effect of hypobaric hypoxia in rat heart through rebalancing NO and arginase 1 signaling pathways [14], and protects HUVECs from high glucose challenge via AMPK-AKT-eNOS-NO signaling pathway [15]. In addition, NO has been reported to maintain cytoskeletal structure and suppress apoptosis in endothelial cells [32,33].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study, we observed that RCE rescued endothelial NO production and signaling via AMPK-AKT-eNOS axis under hypoxia. This is consistent with our previous studies demonstrating that RCE counteracts the effect of hypobaric hypoxia in rat heart through rebalancing NO and arginase 1 signaling pathways [14], and protects HUVECs from high glucose challenge via AMPK-AKT-eNOS-NO signaling pathway [15]. In addition, NO has been reported to maintain cytoskeletal structure and suppress apoptosis in endothelial cells [32,33].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, R. crenulata might be beneficial for many vascular diseases related to hypoxic damage and NO dysfunction in the endothelium. In the case of OSA, RCE may offer additional benefits because OSA is associated with poor glycemic control [34], and RCE has shown protective effects in this context [15,35]. Based on this finding, RCE might be considered a potential agent for vascular disorders in diabetic patients with OSA syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations